2019
DOI: 10.1039/c9sc00857h
|View full text |Cite
|
Sign up to set email alerts
|

Self-promoted and stereospecific formation of N-glycosides

Abstract: A stereoselective and self-promoted glycosylation for the synthesis of various N-glycosides and glycosyl sulfonamides from trichloroacetimidates is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 50 publications
4
36
0
Order By: Relevance
“…Stereoselective self-promoted O-glycosylation with TCA donors has been known for decades [23][24][25][26][27][28] and recently, we demonstrated that N-sulfonyl carbamates are acceptors in selfpromoted N-glycosylations (Scheme 1b). [29] As the glycosylations are highly stereospecific, and the TCA donors can be synthesized in a stereoselective manner, [30] one can influence the stereochemical outcome in the glycosylation already in the donor synthesis. Besides access to interesting N-glycosides the self-promoted glycosylations are also interesting when studying the glycosylation mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Stereoselective self-promoted O-glycosylation with TCA donors has been known for decades [23][24][25][26][27][28] and recently, we demonstrated that N-sulfonyl carbamates are acceptors in selfpromoted N-glycosylations (Scheme 1b). [29] As the glycosylations are highly stereospecific, and the TCA donors can be synthesized in a stereoselective manner, [30] one can influence the stereochemical outcome in the glycosylation already in the donor synthesis. Besides access to interesting N-glycosides the self-promoted glycosylations are also interesting when studying the glycosylation mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…In this account we try to unravel which features that make a system self‐promoted and what effects that govern the stereochemical outcome of such self‐promoted glycosylations. Work done within this field of glycosylation chemistry will be presented and combined with descriptions of our own experiences in this field, where we have recently developed a new method for self‐promoted stereospecific N ‐glycosylations [11] . First examples of self‐promoted O ‐glycosylations utilizing imidate donors and imidate‐like donors are introduced.…”
Section: Introductionmentioning
confidence: 99%
“…One of the major advantages of using trichloroacetimidates is the selective accessibility of either their α-or β-anomers, which has previously been utilized by Schmidt [26][27][28][57][58][59] and ourselves. 37 To investigate whether the pyrylium-catalysts also engaged in similar stereospecific glycosylations, we carried out a series of glucosylations and galactosylations (Scheme 4, top and middle) using the corresponding β-trichloroacetimidates. It was found that Me3Pyry was in fact a superior catalyst over H3Pyry for α-glycosylations, resulting in high degrees of stereoselectivity for both parent sugars at ambient conditions.…”
Section: Resultsmentioning
confidence: 99%
“…This discovery was made via a hypothesis-based investigation as we sought out to identify a catalytic species capable of lowering the pKa value of alcohols to the 3-5 range that we previously found ideal for stereospecific, selfpromoted N-glycosylations. 37,38 This led to the discovery that pyrylium salts are capable of providing such catalyst-nucleophile interactions, resulting in stereospecific O-glycosylations of trichloroacetimidate electrophiles with a wide range of phenols and alkyl alcohol nucleophiles. Many 4 pyrylium salts are commercially available and have gained interest in the scientific community as organic dyes 39,40 and photoredox catalysts, [41][42][43] and were recently introduced as catalysts for Katritzky-like C-N bond activations [44][45][46] by Cornella and co-workers.…”
Section: Introductionmentioning
confidence: 99%